2020
DOI: 10.5114/pjr.2020.95477
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the neglected segment of the intestine: the duodenum and its pathologies

Abstract: Herein we reviewed the computed tomography (CT) findings of a spectrum of pathological entities affecting the duodenum. We discuss the CT findings of some congenital, inflammatory, traumatic, and neoplastic pathologies of the duodenum along with the conventional barium studies of selected conditions. Pathologies of this C-shaped intestinal segment, derived from both foregut and midgut, are often overlooked in clinical practice and radiological literature. While congenital anomalies like duplication cysts and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The third part is horizontal and crosses from right to left. The fourth part is located left to the abdominal aorta and ascends to the level of the second lumbar vertebra and ends at the duodenojejunal junction 14 . Although a double bubble usually represents a duodenal obstruction, two bubbles with an intervening normal duodenal segment are suspicious for a duodenal duplication cyst.…”
Section: Discussionmentioning
confidence: 99%
“…The third part is horizontal and crosses from right to left. The fourth part is located left to the abdominal aorta and ascends to the level of the second lumbar vertebra and ends at the duodenojejunal junction 14 . Although a double bubble usually represents a duodenal obstruction, two bubbles with an intervening normal duodenal segment are suspicious for a duodenal duplication cyst.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its non-specific symptoms, SMA syndrome might be overlooked in clinical practice[ 26 , 91 ]. Even in radiologists, the duodenum seems to be a neglected segment in the intestine[ 92 ]. SMA syndrome requires a high degree of clinical suspicion and few teaching methods have been reported[ 93 , 94 ].…”
Section: Diagnosismentioning
confidence: 99%
“…The duodenum, 25-30 cm in length, is the widest portion of the small bowel and is divided into four parts (1)(2)(3). The first part of the duodenum consists of the 2.5-cm-long intraperitoneal segment as a continuation of the pylorus, which is called the duodenal bulb, and the 2.5-cm-long retroperitoneal segment, which ends at the superior duodenal flexure (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The duodenum, 25-30 cm in length, is the widest portion of the small bowel and is divided into four parts (1)(2)(3). The first part of the duodenum consists of the 2.5-cm-long intraperitoneal segment as a continuation of the pylorus, which is called the duodenal bulb, and the 2.5-cm-long retroperitoneal segment, which ends at the superior duodenal flexure (1)(2)(3). Regarding the blood supply to the duodenal bulb, which is the portion utilized in anastomosing the duodenum and remnant stomach following distal gastrectomy, Hentati et al (4) reported that all of the arterial pedicles reached the duodenal bulb on its posterior wall and thereafter spread along its anterior wall.…”
Section: Introductionmentioning
confidence: 99%